ERODIBILITY STUDY OF MINING AREA, CASE STUDY: WASTEDUMP DISPOSAL OF ASAM-ASAM SITE, PT. ARUTMIN INDONESIA - ROZAQ, FATHUR
Erosion (from the Latin erodere) is manifested by the deterioration of soil surface effected by exogenous forces, especially water, ice, wind and man as the significant anthropogenic factor. The presence of erosion on the soil surface will result in the loss of some material from the soil due to the kinetic energy of the exogenous forces. Rainwater that falls on the surface of the soil will pound the aggregate of soil into loose soil particles. These released soil particles will be carried by the surface stream (Hakim, 1986). Asam-Asam Site disposal’s have a considerable dimension (500 Ha). The disposal can be divided inti active and reclamation areas. According Riquier (1977) erosion that occurs in the embankment area can exacerbate the characteristics of maerial properties, smooth out drainage channels and disrupt the stability of the slope so it needs to be minimized. Knowing the erosion burden that will occur in a region is important because it can provide information about the amount of material transported and solutions to the problem can be determined. In this research, USLE (Universal Soil Loss Equation) method is used to predict the erosion load and Carsten method (1966) to predict the critical speed of erosion cause. The results of this study indicate the erosion loads occurring in the Asam-Asam Site is 120 to 1100 t/Ha/yr for active disposal’s zone, and 2-130 t/Ha/yr for reclamation disposal’s zone which depending on material physical properties, slope dimensions, vegetation and land management.